1961
DOI: 10.1071/ch9610662
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoids from the Bark of Avicennia marina

Abstract: Avicennia marina, commonly known as the grey mangrove, is distributed widely along the coast of New South Wales. It is used as a source of tannin in some countries and the very hard timber is used occasionally in boat-building. The bark has now been examined for neutral and acid constituents and was found to contain betulic acid (0 -3 %), taraxerol (0 -06 %), and taraxerone (0.05 %).A minute amount of a hydrocarbon, probably triacontane, was also isolated. ExperimentalMelting points are uncorrected and were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Other biological activities showed that 6 and 7 were also allelopathic [46] and displayed anti-fungal activity [47]. Meanwhile, the only difference between compound 8 and 9 is the presence of a double bond on the side chain at ∆ 22,23 . Compound 8 which possessed a saturated side chain was inactive against T. b. brucei with an MIC value of 142.30 µM.…”
Section: Anti-trypanosomal and Cytotoxic Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other biological activities showed that 6 and 7 were also allelopathic [46] and displayed anti-fungal activity [47]. Meanwhile, the only difference between compound 8 and 9 is the presence of a double bond on the side chain at ∆ 22,23 . Compound 8 which possessed a saturated side chain was inactive against T. b. brucei with an MIC value of 142.30 µM.…”
Section: Anti-trypanosomal and Cytotoxic Activitiesmentioning
confidence: 99%
“…revealed lapachol, a naphthofuranquinone compound which has been isolated from Indian and West African A. tomentosa [ 6 ]. Later, various classes of chemical components have been isolated from the Avicennia genus, including naphthoquinones [ 7 , 8 , 9 , 10 , 11 ], iridoid glucosides [ 12 , 13 , 14 , 15 , 16 , 17 ], sterols [ 18 , 19 ], flavones [ 16 , 20 ], diterpenes [ 21 ] and triterpenes [ 18 , 19 , 22 , 23 ] from leaves, roots, twigs and stem bark.…”
Section: Introductionmentioning
confidence: 99%
“…Avicennia marina is one of the most important mangrove plants that have gained more attention because of its medical importance [3, 4]. Indeed, the study of the medical importance of A. marina started early when Bell and Duewel [5] isolated triterpenoids from the bark of A. marina . These terpenoids were later identified as lupeol, taraxerol, and betulinic acid [6].…”
Section: Introductionmentioning
confidence: 99%
“…Since Bell et al [5] first reported the isolation of triterpenoids from different parts of AM, more than sixty compounds have been isolated from this plant species [6]. The versatility and adeptness to grow in conditions of high salinity, high temperatures, anaerobic soil, strong winds and changing ocean tides allow mangroves to produce a rich source of interesting metabolites.…”
Section: Introductionmentioning
confidence: 99%